Exploratory study on detection of drug resistance of Mycobacterium tuberculosis in sputum specimens by next-generation sequencing - Liu, Y Y; Shi, J; Chu, P; Wu, T Y; Li, L; Pang, Y; Lu, J; Guo, Y L (Zhonghua jiehe he huxi zazhi, 2022)
To compare the diagnostic performance of next-generation sequencing (NGS) detection methods in sputum samples and strains, in order to explore the feasibility of the NGS method to detect drug resistance in sputum specimens. In this retrospective study, the sputum specimens and corresponding clinical isolates of 50 pulmonary tuberculosis patients admitted to Beijing Chest Hospital from January 2017 to December 2017 were collected. The gene mutations of , , , , , , , , and in sputum specimens and corresponding clinical isolates were detected by NGS method. The phenotypic drug susceptibility test (DST) of the strains was carried out by the proportion method. Using DST results as a reference, the sensitivity, specificity, positive predictive value and negative predictive value of the NGS method for clinical strains and sputum specimens, as well as the consistency statistic ( ) with phenotype DST were calculated respectively. The Chi-square test was used to compare the accuracy of the NGS testing in sputum samples